(untitled) (Teaching and Learning Inquiry, 2016)
Linguistic, literary, and feminist studies define translation as a process of rendering a new version of an original with attention to context, power, and purpose. Processes of translation in the context of student-faculty co-inquiry in the Scholarship of Teaching and Learning offer examples of how this re-rendering can play out in the realm of academic development. In this article, translation serves as a conceptual framework that allows us to bring a fresh interpretation to the collaborative work of participants in a student-faculty pedagogical partnership program based at two colleges in the mid-Atlantic United States. We argue that faculty members and student consultants who participate in this program engage in processes of translation that lead to transformed perceptions of classroom engagement, transformed terms for naming pedagogical practices, and, more metaphorically, transformed selves. Drawing on data from an ongoing action research study of this program and on articles and essays we and other participants in the program have published, we use a form of narrative analysis as it intersects with the conceptual framework offered by translation to illustrate how, through their collaboration, faculty and students engage in never-finished processes of change that enable mental perceptions, linguistic terms, and human selves to be newly comprehended, communicated, and expressed. We touch upon what is lost in translation as well and the necessity of ongoing efforts to make meaning through collaborative explorations, analyses, and re-renderings. Finally, we provide examples of how the changes participants experience and effect endure beyond the time of partnership and in other realms of their lives.